Teaching theory and practice - a pre-university teacher's dilemma - Nesa Ramani Ganesan, *; Alagarajah K. Thavarajah, * (Sunway University College, 2010)
This study was aimed to investigate the application of teaching and learning theories that were applied during the teaching and learning process. There are many teaching theories that advocates that the best learning technique is student-based or student-centred learning. Selected teachers were interviewed based on their teaching experience and education background. Three main groups of teachers were studied; those who had more than 20 years of teaching experience, those who had between ten to twenty years teaching experience and those with less than ten years. The Pre-University programmes chosen were those with at least fifty percent external examination component such as A-levels, MUFY and the AUSMAT. This article is written based on the teachers? experiences and the problems that arise as they tried to apply the teaching and learning theories that were taught during their training as a teacher.